O sistema termodinâmico do clima urbano de Nova Palma, RS: contribuição ao clima urbano de cidades pequenas - Rossato, Paula Savegnago (2010)
In recent years, people have been carried through small studies of urban climate focusing small and average cities, with intention to diagnosis and to prevent the possible problems that these cities can come to face in the future to if becoming cities of bigger transport the study will be carried through in Nova Palma to verify which is the configuration of some elements of the climate, as temperature of air, relative humidity of air and direction of the wind, in cities where the urban space is reduced. The city of Nova Palma presents a territorial extension of 362,48Km ² and population of 6.444 inhabitants, being who of these only 3Km ² are of urban area (headquarters), where inhabits 2,664 inhabitants. The research was made in accordance with the proposal of Monteiro (1976) to study the climate of a city, the System Urban Climate, considered for this study the thermodynamic subsystem, that has as main elements the relative humidity of air, the temperature of air and the wind. Through points of comment installed in the interior of the city and its proximity, its had been collected the data of the main elements of the thermodynamic subsystem in three schedules and for a period of 5 days consecutive in each one of the four seasons of the year of 2008. The area is understood here as proximity that is inside of the urban perimeter of Nova Palma, but that not yet it is urban. In the four stations of the year the thermodynamic elements if they had defined, firstly, for the sazonais characteristics, after that for the operating atmospheric system and later for the geoecológicos and geourbanos condicionantes previously mentioned. It was also observed, to if analyzing the data of the Station Meteorológica of Santa Maria, that Nova Palma always presented, in the days of referring collection to the four seasons of the year, minims of lesser temperatures, maximum greaters and raised relative humidity more registered than the values in the Station of the INMET (National Institute of Meteorologia).